Resurrecting the genus Geomorium: Systematic study of fungi in the genera Underwoodia and Gymnohydnotrya (Pezizales) with the description of three new South American species - Kraisitudomsook, N. (2020)
Molecular phylogenetic analyses have addressed the systematic position of several major Northern Hemisphere lineages of Pezizales but the taxa of the Southern Hemisphere remain understudied. This study focuses on the molecular systematics and taxonomy of Southern Hemisphere species currently treated in the genera Underwoodia and Gymnohydnotrya. Species in these genera have been identified as the monophyletic /gymnohydnotrya lineage, but no further research has been conducted to determine the evolutionary origin of this lineage or its relationship with other Pezizales lineages. Here, we present a phylogenetic study of fungal species previously described in Underwoodia and Gymnohydnotrya, with sampling of all but one described species. We revise the taxonomy of this lineage and describe three new species from the Patagonian region of South America. Our results show that none of these Southern Hemisphere species are closely related to Underwoodia columnaris, the type species of the genus Underwoodia. Accordingly, we recognize the genus Geomorium described by Spegazzini in 1922 for G. fuegianum. We propose the new family, Geomoriaceae fam. nov., to accommodate this phylogenetically and morphologically unique Southern Hemisphere lineage. Molecular dating estimated that Geomoriaceae started to diverge from its sister clade Tuberaceae c. 112 MYA, with a crown age for the family in the late Cretaceous (c. 67 MYA). This scenario fits well with a Gondwanan origin of the family before the split of Australia and South America from Antarctica during the Paleocene-Eocene boundary (c. 50 MYA).